A benefit of high temperature increased effectiveness of a rice bacterial blight disease resistance gene - Webb, K M (The New phytologist, 2010)
*Continuous planting of crops containing single disease resistance (R) genes imposes a strong selection for virulence in pathogen populations, often rendering the R gene ineffective. Increasing environmental temperatures may complicate R-gene-mediated disease control because high temperatures often promote disease development and reduce R gene effectiveness. Here, performance of one rice bacterial blight disease R gene was assessed in field and growth chamber studies to determine the influence of temperature on R gene effectiveness and durability. *Disease severity and virulence of Xanthomonas oryzae pv. oryzae (Xoo) populations were monitored in field plots planted to rice with and without the bacterial blight R gene Xa7 over 11 yr. The performance of Xa7 was determined in high- and low-temperature regimes in growth chambers. *Rice with Xa7 exhibited less disease than lines without Xa7 over 11 yr, even though virulence of Xoo field populations increased. Xa7 restricted disease more effectively at high than at low temperatures. Other R genes were less effective at high temperatures. *We propose that Xa7 restricts disease and Xoo population size more efficiently in high temperature cropping seasons compared with cool seasons creating fluctuating selection, thereby positively impacting durability of Xa7